PENGARUH INDEKS KAWASAN REGIONAL TETANGGA (STI, ASX200, KLSE, DAN VN) TERHADAP INDEKS SAHAM GABUNGAN INDONESIA (IHSG) DI BURSA EFEK INDONESIA (BEI) - Sujatmoko Budiarta (PROGRAM PASCA SARJANA MAGISTER MANAJEMEN INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2021)
This research aims to analyse the influence effect of regional that is means neighbour Indonesia country such as Malaysia, Singapore, Australia, and Vietnam to Indonesia Index, that is KLSE, STI, ASX200 and VN Index to IHSG within period June 1, 2021 until July 31, 2021. This research method is recorded and documentation the daily closing index (KLSE, STI, ASX200, VN and IHSG) in period June 1, 2021 until July 31, 2021. The result of this research is KLSE, STI, ASX200, and VN simultaneously significantly influence together to Indonesia Index (IHSG) along June 1, 2021 until July 31, 3021. Index KLSE, STI, and VN not influence to Indonesia Index (IHSG) at Indonesia Stock Exchange along June 1, 2021 until July 31, 2021, only ASX200 can influence Indonesia Index (IHSG) along June 1, 2021 until July 31, 2021.